Large-Scale Model Testing of High-Speed Railway Subgrade under Freeze-Thaw and Precipitation Conditions - Shasha Zhang; Yantao Wang; Fei Xiao; Weizhi Chen (Advances in Civil Engineering)
To determine whether coarse-grained saline soil meets the deformation requirements of the DY high-speed railway subgrade, a study was conducted by a combination of field-monitoring and laboratory tests. First, several temperature sensors were buried vertically in the ground of a typical section, and the temperature at different depths was monitored for nearly one year and analysed dynamically. It was determined that a depth of 4.8 m can be set as the constant-temperature layer. Then, based on the field-monitoring results, laboratory tests were carried out on a large-scale subgrade model under freeze-thaw and precipitation conditions. The change of temperature, moisture content, and soil deformation of the subgrade under long-term freeze-thaw and precipitation conditions were obtained. The results show that the temperature changes periodically with a V shape during the entire cycle. Twenty centimetres below the top surface is the sensitive depth of the sample, and salinity has little effect on temperature change. In the process of cycles, the average moisture content of soils with higher salinity is about 0.5% lower than that of soils with lower salinity. After nine freeze-thaw cycles, the sample finally shows dissolved settlement deformation. Precipitation mainly affects the deformation of the sample; however, the influence on salt-expansion and frost-heave deformation is less significant. Finally, by predicting the deformation of coarse saline soil, it is proven that the soil can meet the deformation requirements of high-speed railway foundations.